Synthesis and determination of Surface tension of 1-butyl-3-methylimidazolium lauroyl sarcosinate IL and Tween 80. Issue 1 (February 2021) - Nazar, Masooma; Shah, Mansoor ul Hassan; Goto, Masahiro; Yahya, Wan Zaireen Nisa; Moniruzzaman, Muhammad
Abstract: Ionic liquids (ILs) have unique physicochemical properties. ILs with long carbon chains are called surface-active ILs, and they have surfactant properties. In this study, we synthesize (1-butyl-3-methylimidazolium lauroyl sarcosinate) [BMIM] [Lausar] IL that have surfactant properties. Nuclear magnetic resonance spectroscopy (NMR) was used to confirm the chemical structure of the synthesized IL. The surface tension of [BMIM] [Lausar] was determined that it was almost 37.1mN/m. Tween 80 is the most famous commercial surfactant, and we also determine the surface tension of Tween 80. Afterword, we make the binary mixture of Tween 80 and IL-based surfactants. Based on our results, we can conclude that Tween 80 and [BMIM] [Lausar] both reduced surface tension and have excellent surface properties when combining and can be used as surfactants in many sectors.